Best practices for artificial intelligence in life sciences research. Issue 5 (May 2021) - Makarov, Vladimir A.; Stouch, Terry; Allgood, Brandon; Willis, Chris D.; Lynch, Nick
Highlights: Use of artificial intelligence (AI) and machine learning (ML) methods in life sciences research calls for best practices. At the core of any AI project should be quality data that are well-understood, consistent and use FAIR principles. Models should be published with code, training and testing data along with scientific results. Research organizations should build skills in quality AI/ML modeling. Abstract : We describe 11 best practices for the successful use of artificial intelligence and machine learning in pharmaceutical and biotechnology research at the data, technology and organizational management levels.